The relationship between the duration time of turn and the throwing record in the men's hammer throw - Hirose, K.; Byn, K. O.; Maeda, K.; Ogata, M. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The aim of this study was to examine the relationship between the duration time of turn and the throwing record. We analyzed the duration time of turn for the 116 men's hammer throwers in the competitions. As a result, significant correlation was observed between the total time of turn and the throwing record (I=-0.83, p<0.001). In addition, the high correlation was observed especially between the total double support phase time and throwing record (r=-0.67, p<0.001), compared to the correlation between the total single support phase time and the throwing record (r=0.29, pc0.01). These results suggest that using the duration time of turn is available for the estimation of the throwing record and shortened the duration time of turn leads to the improvement of the throwing record.